Exploring the role of spiritual leadership among nurse colleagues: an associative analysis of its impact on passion and altruism - Huda Gaber Hamzaa; Mohamed Hussein Ramadan Atta; Heba Mostafa Ali Taha; Mervat Amin Sayed; Asmaa Kamal Ahmed; Ahmed Abdellah Othman; Nadia Mohamed Ibrahim Wahba (BMC Nursing)
Abstract Background Spiritual leadership emphasizes that nurses encounter situations that require compassion, empathy, and a deep understanding of the human experience. Passion can drive nurses' motivation, engagement, and commitment to patient care. Altruism is a core value in nursing that involves selfless concern for the well-being of others. Spiritual leadership might be an essential organizational resource in enhancing followers’ inspiring vision, compassion for others, and passion for their work. Aim of the study To investigate the role of spiritual leadership in the relationship between altruism and passion for work among nurse colleagues. Subjects & method A multicenter descriptive, cross-sectional research study was conducted at six Nursing Egyptian faculties affiliated with Alexandria, Port-Said, Fayoum, Damanhur, Assiut, and Sohag Universities, with 391 nurse colleagues. Data collection tools Personal and Job-related Data Questionnaire, Spiritual Leadership Questionnaire (SLQ), Passion Scale, and 9- Self-Report Altruism Scale (9- SRA) were utilized to collect data. Results The current study verified that nurse colleagues had high levels of perceived spiritual leadership, passion, and altruism (50.9, 47.6, and 40.2, respectively). The results revealed noteworthy positive correlations between spiritual leadership, passion, and altruism (r = 0.644, 0.519, & 0.509). Furthermore, mediation analysis highlighted that spiritual leadership could mediate the effect of altruism on the passion level. Conclusion This study delivers valued insights into the crucial role of spiritual leadership in augmenting nurse colleagues’ altruistic tendencies and passion. Recommendations Cultivating workplace spirituality on a daily agenda is a key component of management that requires spiritual competencies from nurse leaders. These competencies ultimately enhance passion for work, performance, and altruistic behaviors.